Here lies the librarian [compact disc, unabridged] - Peck, Richard, 1934-2018 (Listening Library, 2006)
Fourteen-year-old Eleanor "Peewee" McGrath, a tomboy and automobile enthusiast, discovers new possibilities for her future after the 1914 arrival in her small Indiana town of four young librarians.